Polycystic ovary syndrome: nutrition in the treatment of insulin resistance and inflammatory processes (Research, Society and Development, 2022)
Polycystic ovary syndrome (PCOS) is an endocrine-metabolic syndrome of multifactorial character more common in women in reproductive age. The most commonly observed symptoms are: ovulatory dysfunction, amenorrhea, hyperandrogenism and hirsutism (increased amount of hair). The diagnostic criteria are chronic anovulation, hyperandrogenism and polycystic ovary. The objective of this study was to understand how nutrition works in the treatment of PCOS and its inflammatory processes. The present study was a integrative literature review. The materials were collected through the following databases: SCIELO (Scientific Electronic Library), BIREME (Latin American and Caribbean Center for Health Sciences Information), PUBMED. Included articles from the last 5 years (2017 - 2022). The research was carried out in Portuguese and English. The following types of supplementation were addressed in the management of PCOS: curcumin, omega-3, cinnamon, probiotics, vitamin D, Q10 and vitamin E. The most common benefits found in the studies were related to the increase in QUICKI, reduction in HOMA-IR and in the insulin reduction. Although the various supplements mentioned in this study have had beneficial effects, having a nutricionist working in the intervention of the clinical symptoms of polycystic ovary syndrome is  very important, as it is up to the professional to monitor and help to minimize the symptoms of PCOS and contribute to a better quality of life for these women.